Mini-implants and miniplates generate sub-absolute and absolute anchorage - Alberto Consolaro (Dental Press Editora, 2014)
The functional demand imposed on bone promotes changes in the spatial properties of osteocytes as well as in their extensions uniformly distributed throughout the mineralized surface. Once spatial deformation is established, osteocytes create the need for structural adaptations that result in bone formation and resorption that happen to meet the functional demands. The endosteum and the periosteum are the effectors responsible for stimulating adaptive osteocytes in the inner and outer surfaces.Changes in shape, volume and position of the jaws as a result of skeletal correction of the maxilla and mandible require anchorage to allow bone remodeling to redefine morphology, esthetics and function as a result of spatial deformation conducted by orthodontic appliances. Examining the degree of changes in shape, volume and structural relationship of areas where mini-implants and miniplates are placed allows us to classify mini-implants as devices of subabsolute anchorage and miniplates as devices of absolute anchorage.